The Role of Civil Servant to Protect Indonesia from Terrorism - Roni Efendi; Bambang Trisno; Refika Mastanora; Ratmiati Ratmiati; Agusrida Agusrida; Raihanah Abdullah (Alfuad: Jurnal Sosial Keagamaan, 2022)
The State Civil Apparatus (ASN) is an occupation for civil servants and government employes with employment contracts who work for government agencies and play a very fundamental role in maintaining the unitary state of the Republic of Indonesia. ASN urgencies include the implementation of public policies, civil servants and the connected the nation must be able to act as organizers of government and developmental missions through the implementation of policies and professional public services. In fulfilling its function as a link and unification of the nation, ASN must strive to protect the integrity of the unitary state of the Republic of Indonesia from terrorism crimes that can break the sovereignty anchored in Bineka Tunggal Ika. Dirrect speak and written expressions of opinions on social media don’t contain elements of hate speech against to Pancasila, the Constitution, Bhineka Tunggal Ika, the Unified State of the Republic of Indonesia and the government. Don’t convey information that shows the nuances of hate speech against ethnicity, race, religion, and between groups. ASN doesn’t participate in activities that lead to insult, incitement, provocation or hatred of Pancasila, the Constitution, Bhineka Tunggal Ika, the Unified State of the Republic of Indonesia and the government.